KEBERADAAN TITIK TETAP PADA RUANG BANACH-2 - MARIS, IKA METIZA (Sainstek : Jurnal Sains dan Teknologi, 2013)
On finite dimensional, in this paper will show that 2-Banach Space is a Banach space. This is prove by use Cauchy sequence end convergence properties. Then will be show the e. xistence of fixed point in 2-banach space, with the first proving existence of fixed point in banach space. Key words: banach space, banach space -2, fixed point